THE INFLUENCE OF GOVERNMENT ACCOUNTING STANDARDS IN QUALITY FINANCIAL MANAGEMENT AT REGIONAL GOVERNMENT OF BONE DISTRICT (CASE STUDY OF REGIONAL REVENUE AGENCY) - Kasifah, Nur; Muhammad Idrus, Idrus; Nurkurnia, Nurkurnia (LPPM Universitas Muhammadiyah Mamuju, 2023)
Research Objectives: To determine and analyze the application of government accounting standards (SAP) which influences the quality of government financial reports at the Bone Regency Regional Revenue Agency, to determine the accounting basis used by the Government Accounting Standards (SAP) for the Bone Regency Regional Revenue Agency. This research uses quantitative methods to measure the quality of government financial reports at the Bone Regency Regional Revenue Agency. Research results 1) Government accounting standards have a significant effect on the quality of financial reports in a positive direction at the Bone Regency Regional Revenue Agency. 2) The better implementation of government accounting standards will be accompanied by the quality of financial reports. In other words, government accounting standards will help improve the quality of financial reports at the Bone Regency Regional Revenue Agency. 3) The results of this research prove that if the score of government accounting standards increases by 1 (one) unit, there will be an increase in the quality of financial reports